(untitled) (Environment & Health, 2018)
Objective: We studied the hygienic issues of the safety of modern motor filling stations (MFS) and developed the measures for the minimization of the hazardous impact of their functioning on the environment of residential areas. Methods: We applied the method of expert assessment, method of sanitary-and-epidemiological examination, sanitary-and-hygienic, analytical, sanitary-and-statistical ones. Results: Results of the complex investigations on the hygienic safety of modern MFS of small and middle power by the level of their impact on the contamination of the environment are presented in the article. Conclusions: Normative sanitary-and-protective zone of 50 m is sufficient for motor filling station of small and middle power by the criteria: exist of modern motor park; exist of modern equipment with fire-preventive technologies; adherence to the concentrations of the pollutants and levels of hazardous factors not exceeding their hygienic standards on the external boundaries of sanitary-and-protective zones near residential building; level of the supply with sanitary-and hygienic conditions for the labour of MFS workers and consumers; improvement and planting of greeneries of MFS territories; organization of entry and exit groups at the MFS territories taking into account sanitary gaps; implementation of the measures for the prevention of psychogenic load on the residents of the adjoining building.